A new multichannel MAC protocol for ad hoc networks based on two-phase coding with power control (TPCPC) - Zhang, Lili (2011)
This paper presents a new CDMA-based multichannel medium access control protocol for ad hoc networks, which is named as two-phase coding multichannel protocol with power control. The first phase code is used to broaden the area reuse and the second phase code is employed to distinguish between different nodes in one specific area. This algorithm efficiently eliminates hidden terminal and exposed terminal problems during data transmission and greatly increases the throughput. In addition, it has good scalability and can be easily accomplished with GPS. Although many multichannel MAC protocols adopting CDMA techniques have been presented, few have addressed the near-far problem. We incorporate power control in our algorithm and reduce the near-far interference. The implementation of two-phase coding with power control is discussed, and the primary simulation result demonstrates that the proposed protocol offers better performance.